2018
DOI: 10.1016/j.fertnstert.2018.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing reveals differentially expressed small noncoding RNAs in uterine leiomyoma

Abstract: Our results provide the first evidence for the differential expression of additional classes of sncRNAs and AGO2 in leiomyoma, implicating their roles as a gene regulatory mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 68 publications
(73 reference statements)
0
15
0
1
Order By: Relevance
“…Immunoblotting. Immunoblotting was performed following previously described methods (15,18). Briefly, samples were suspended in RIPA buffer containing 1 mM EDTA and EGTA (Boston BioProducts, Ashland, MA) supplemented with 1 mM PMSF and a complete protease inhibitor mixture (Roche Diagnostics, Indianapolis, IN), sonicated, and centrifuged at 4°C for 10 min at 14,000 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblotting. Immunoblotting was performed following previously described methods (15,18). Briefly, samples were suspended in RIPA buffer containing 1 mM EDTA and EGTA (Boston BioProducts, Ashland, MA) supplemented with 1 mM PMSF and a complete protease inhibitor mixture (Roche Diagnostics, Indianapolis, IN), sonicated, and centrifuged at 4°C for 10 min at 14,000 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…Total protein isolated from LSMC following treatment conditions was subjected to immunoblotting as previously described (12,37). Briefly, samples were suspended in RIPA buffer containing 1 mmol/L EDTA and EGTA (Boston Bioproducts) supplemented with 1 mmol/L PMSF and a complete protease inhibitor mixture (Roche Diagnostics), sonicated, and centrifuged at 4 C for 10 minutes at 14,000 rpm.…”
Section: Immunoblottingmentioning
confidence: 99%
“…Accumulated proteomic and genomic studies have indicated that altered expression of small noncoding RNAs, including microRNAs (miRNAs), play a key role in cellular events leading to leiomyoma development and growth (5,(8)(9)(10)(11)(12). More specifically, our laboratory and others have provided evidence that the expression of the miR-200 and miR-29 family are suppressed in leiomyoma and that their altered expression accounts at least in part for the molecular mechanism underlying ECM accumulation, angiogenesis, and inflammation (13)(14)(15)(16)(17).…”
mentioning
confidence: 96%
“…Uterine leiomyoma (UL) are the common benign neoplastic disease among women worldwide. Screening the RNA-sequencing data with the sncRNA database leaded to the findings that 24 piRNAs were differentially expressed by more than 1.5 fold in UL compared to adjacent normal myometrium [89]. For future study, it would be interesting to determine their molecular functions in the UL.…”
Section: Pirnas In Other Types Of Diseasesmentioning
confidence: 99%